Desempenho, características de carcaça e da carne de cordeiros de diferentes genótipos terminados em confinamento - Rocha, Luciana Porangaba (2013)
The objective of this study was to evaluate the performance, quantitative and qualitative characteristics of the carcass and meat quality traits of lambs Santa Inês x undefined breed, Dorper x undefined breed e undefined breed feedlot and fed a unique diet. A total of 30 lambs, 10 in each genotype, with an average age of 150 days and an average live weight of 19.3 ± 2.6 kg. We used a total mixed ration containing 15.5% crude protein and 2.58 Mcal / kg DM, in the proportion 35:65 (forage:concentrate). Genotype influenced the performance of lambs, gross profit margin, the quantitative and qualitative characteristics of the carcass and meat quality. The crossbred Dorper x undefined breed and Santa Inês x undefined breed fared better over the final weight, with higher tissue accumulation during the period of confinement greater total weight gain, improved feed conversion and daily showing similar behavior. Among the quality and quantitative carcass conformation and weight of the cuts of the crossbred Dorper x undefined breed showed better results. The crossbred Dorper x undefined breed and Santa Ines x undefined breed had higher slaughter weight, however the crossbred Dorper x undefined breed had better hot carcass weight, ribeye area, leg muscularity and carcass compactness index. The different genotypes have similar tissue components leg. genotypes Dorperx undefined breed and Santa Inês x undefined breed had higher protein content and lower lipid content and cholesterol in meat. The intensity of luminosity L * and a* was higher in the undefined breed and his crossbred with Dorper. The fatty acids found in greater proportion in Longissimus muscle of lamb meat from different genotypes were C16:0, C18:0 and C18:1. Of the sensory attributes of lamb meat, genotype exerted influence on the color red raw. The crossbred lambs Santa Inês x undefined breed and Dorper x undefined breed present great potential for the production of meat with good nutritional value.